The level of anxiety of 3rd level students of the Diploma three Nursing Study Program in carrying out hospital practices during the Covid-19 pandemic - Ariani Sulistyorini; Nurlaili Fitriani (Universitas Muhammadiyah Jember, 2022)
Background and Aim :The Covid-19 virus has been set to become a pandemic since mid-March 2020, which has hampered the student learning process, one of which is during hospital clinical practice. The possibility of being infected is quite high while in the hospital environment, which has an impact on the occurrence of anxiety in students. The purpose of the study was to determine The level of anxiety of 3rd level students of the Diploma three Nursing Study Program in carrying out hospital practices during the Covid-19 pandemic.Methods: The research used Crossectional Descriptive design, population and research sample of all level 3 students of the Diploma three Nursing Study Program, namely 70 respondents with Total Sampling techniques. The study was conducted on February 1-28, 2022, with research variables on student anxiety levels in carrying out hospital practices during the Covid-19 pandemic, the research instrument of the HARS Scale (Hamilton Anxiety Rating Scale) questionnaire, the data that has been collected is then analyzed with a Frequency distribution table and quantitatively interpreted.Results: The results of the study of 70 respondents found that half of the respondents, namely 35 respondents (50%) experienced mild anxiety, almost half of the respondents, namely 25 respondents (36%) experienced moderate anxiety, a small part of the respondents, namely 8 respondents (11%) had no anxiety and 2 respondents (3%) experienced severe anxiety.This anxiety is caused by several factors, namely age, gender, place of residence, previous practice experience, personal protective equipment used, history of vaccinations that have been carried out and sources of information about Covid-19.Conclusion: Educational institutions are expected to provide information on good coping mechanisms to overcome student anxiety. Students are expected to be able to apply effective coping mechanisms that have been obtained such as relaxation to reduce anxiety levels when carrying out clinical practice in hospitals.